2017
DOI: 10.3390/f8090302
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Monitoring Forest Degradation in a Deciduous Tropical Forest in Mexico via Remote Sensing Indicators

Abstract: Assessing and monitoring forest degradation under national Monitoring, Verification and Reporting (MRV) systems in developing countries have been difficult to implement due to the lack of adequate technical and operational capacities. This study aims at providing methodological options for monitoring forest degradation in developing countries by using freely available remote sensing, forest inventory and ancillary data. We propose using Canopy Cover to separate, through a time series analysis approach using La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 73 publications
1
19
0
Order By: Relevance
“…However, since many of these classifiers presented overlapping thresholds between very different classes, it is clear that they can not be configured as absolute descriptors of each class. For instance, analysts may need different class definition in their studies, or their definition may be based on criteria like above-ground biomass, Net Primary Productivity, forest stand volume, basal area, average stand height, diameter at breast height, age and/or many others, as used by studies such Lu et al [3], Vieira et al [69], Salomão et al [70] and Romero-Sanchez and Ponce-Hernandez [74] to justify the subdivision of secondary vegetation classes. Nonetheless, many of these classifiers are implemented and the users are free to further describe the classes or even to include new subclasses, without compromising the use of the proposed hierarchical class system.…”
Section: Discussionmentioning
confidence: 99%
“…However, since many of these classifiers presented overlapping thresholds between very different classes, it is clear that they can not be configured as absolute descriptors of each class. For instance, analysts may need different class definition in their studies, or their definition may be based on criteria like above-ground biomass, Net Primary Productivity, forest stand volume, basal area, average stand height, diameter at breast height, age and/or many others, as used by studies such Lu et al [3], Vieira et al [69], Salomão et al [70] and Romero-Sanchez and Ponce-Hernandez [74] to justify the subdivision of secondary vegetation classes. Nonetheless, many of these classifiers are implemented and the users are free to further describe the classes or even to include new subclasses, without compromising the use of the proposed hierarchical class system.…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative to consider land use change and land cover dynamics to promote conservation strategies for each species. The Mexican territory suffers fragmentation, disturbances, and some degradation processes [59][60][61], causing changes in the structure, function, composition, productivity, and extent of forests that may contribute to the diminishing of forest species [62,63].…”
Section: Final Considerationsmentioning
confidence: 99%
“…Therefore, for L = 1, SAVI approaches perpendicular vegetation index (PVI), which uses the perpendicular distance from each pixel coordinate to the soil line, while for L = 0, SAVI is equal to NDVI [37]. Many studies have identified the usefulness of long series of vegetation indices (mainly NDVI) derived from satellite data for monitoring purposes of forest degradation, but most have been based on low-to medium-resolution satellite images (e.g., [38][39][40]).…”
Section: Introductionmentioning
confidence: 99%